2020
DOI: 10.1026/0049-8637/a000231
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination Among Youth of Immigrant Descent in Germany

Abstract: Abstract. Ethnic discrimination has a negative impact on the socioemotional, behavioral, relational, and academic adjustment of adolescents, while belonging with classmates, teachers, heritage, and national group may promote positive socioemotional and academic adjustment. We investigate (1) whether greater discrimination by peers and a lower sense of belonging with classmates, teachers, heritage group, and national group are associated with lower socioemotional and academic adjustment of adolescents of immigr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 55 publications
(98 reference statements)
0
14
0
Order By: Relevance
“…Our findings with this cohort of Australian refugee background youth were not dissimilar to those of minority youth in Canada, where the impact of cultural identity on resilience was significant [ 81 ]. The positive influence of ethnic or cultural identity and belongingness has been noted elsewhere, for example, with immigrant adolescents in Germany [ 82 ]. These studies in Canada and Germany, in addition to the study presented here with refugee background youth in Australia, suggest that it is maintenance of connections to ethnic cultural heritage that are most crucial.…”
Section: Discussionmentioning
confidence: 85%
“…Our findings with this cohort of Australian refugee background youth were not dissimilar to those of minority youth in Canada, where the impact of cultural identity on resilience was significant [ 81 ]. The positive influence of ethnic or cultural identity and belongingness has been noted elsewhere, for example, with immigrant adolescents in Germany [ 82 ]. These studies in Canada and Germany, in addition to the study presented here with refugee background youth in Australia, suggest that it is maintenance of connections to ethnic cultural heritage that are most crucial.…”
Section: Discussionmentioning
confidence: 85%
“…One, it can foster a sense of belonging and clarity regarding one's own ethnic-racial group and thus identification with that group (Huguley, Wang, Vasquez, & Guo, 2019). This is important because studies find that German adolescents of immigrant descent with a stronger and clearer understanding of their heritage culture identity do better in school (Schachner et al, 2014;Spiegler, Sonnenberg, Fassbender, Kohl, & Leyendecker, 2018), are socioemotionally better adjusted (Kunyu et al, 2020;Schotte, Stanat, & Edele, 2018), and have more positive other-group attitudes (Juang, Schachner, Pevec, & Moffitt, 2020).…”
Section: What Does Family Ethnic-racial Socialization Do?mentioning
confidence: 99%
“…When German adolescents of immigrant descent experience discrimination, supportive relations with teachers (Civitillo et al, 2021) and a positive classroom climate (Brenick et al, 2018) can be protective factors. Adolescents who have a stronger sense of belonging with their heritage culture (e.g., stronger heritage culture identity) also have weaker relations between discrimination and poorer socioemotional and academic adjustment (Kunyu, Juang, Schachner, & Schwarzenthal, 2020). These findings are in line with a meta‐analysis of 56 studies (mostly from the U.S., 90%) showing that this belonging dimension of ethnic‐racial identity (and not the exploration dimension) can be protective (Yip, Mootoo, Wang, & Mirpuri, 2019).…”
Section: What Do We Know and What Areas Are Understudied?mentioning
confidence: 99%
“…To go beyond testing measurement properties and provide evidence for substantive relations, we also test whether foreigner objectification is related to life satisfaction and various aspects of school well-being. Based on studies in Germany showing a link between perceived discrimination and poorer psychological and academic well-being (Kunyu et al, 2020;Brenick et al, 2018;Civitillo et al, 2021;Schachner et al, 2018), we expect that the FOBS will relate negatively to subjective school values, school competence beliefs, and life satisfaction, and positively to behavioral school disengagement. Further, previous studies found that adolescents experiencing greater discrimination tend to adopt a stronger ethnic identity based on the rejection-identification hypothesis (Branscombe et al, 1999;Yip, 2018), which suggests that experiencing rejection from the broader society or others of different ethnic heritage leads to people turning toward their own group to reinforce their self-esteem.…”
Section: Applying and Examining The Foreigner Objectification Scalementioning
confidence: 99%
“…Among German adolescents of migration background more broadly, greater discrimination is related to poorer academic achievement (Schachner et al, 2018). It is also important to highlight that German adolescents of migration background are aware of and resist these experiences of discrimination (Mansel & Spaiser, 2010;, and that the negative effects of discrimination are weakened for adolescents who have a strong connection to their heritage cultural 2 identity (Kunyu et al, 2020), experience a supportive classroom climate (Brenick et al, 2018), and have a positive relationship with their classroom teacher (Civitillo et al, 2021).…”
mentioning
confidence: 99%